Photophysiology of potential chloroplast macroalgal donors to the sea slug Elysia viridis and its kleptoplasts - Fernandes, Ana Margarida Marques (2023)
Some sea slugs from the group Sacoglossa have a particular ability known as kleptoplasty i.e., the capacity to “steal” and use chloroplasts (herein kleptoplasts) from the algae they eat. Kleptoplasts can remain functional for variable time span however, the time of the retain chloroplast can vary depending on the type of macroalgae they feed on. Moreover, the physiological aspects of the algae species have an impact on chloroplast maintenance. In this work five macroalgae species were studied concerning their different photosynthesis and photoprotection characteristics. Additionally, the physiology of Elysia viridis feeding on two different marcoalgae, Codium tomentosum and Bryopsis sp. was investigated. The results showed that sea slug diet had a great impact on growth rate and chloroplast maintenance. Also, Bryopsis sp. appeared to be a more favourable alternative food source to C. tomentosum, presenting better growth rates and photosynthetic activity during both feeding and starvation periods. Furthermore, the presence of photoprotective mechanisms was confirmed in three of the five species (Acetabularia acetabulum, Cladophora sp. and Vaucheria litorea) studied and it was showed the absence of a photoprotective mechanism in the Bryopsidales species C. tomentosum and Bryopsis sp..